Біологічні зразки для експертизи: поняття, умови, тактика відбирання - Щербаковський, М. Г.; Shcherbakovskyi, M. H.; Проценко, А. М.; Protsenko, A. M.; Волкова, А. Е.; Volkova, A. E.; Михайло Щербаковський (Вісник Харківського національного університету внутрішніх справ. – 2024. – № 2 (105), ч. 1. - С. 189-203, 2024)
Доведено, що біологічними зразками для експертизи є частини (тканини), виділення та відбитки рельєфу шкіри тіла людини. Визначено обов’язкових і факультативних учасників, умови та загальний алгоритм тактики добровільного та примусового відбирання біологічних зразків для експертизи на стадії досудового розслідування, який включає підготовчий, робочий та заключний етапи проведення процесуальної дії.

During the commission of crimes, traces of biological origin are left on the objects of the environment, tools, clothing, and the body of the participants. To conduct an identification study, an expert needs to compare the traces of the crime with biological samples of the person being tested. Criteria for determining biological samples are proposed. The biological criterion means that the samples reflect the internal and external properties of a person as a biological organism. The informational criterion is that the samples meet certain requirements: undoubted origin, required quantity, proper quality, compatibility with traces of crime. The identification criterion establishes that the human properties reflected by the samples are individual, stable, cannot be deliberately altered by a person and are suitable for identification. The procedural criterion means that biological samples must be collected in a lawful manner. Based on these criteria, biological samples for examination include: body parts; secretions as products of human activity; imprints of the skin relief of the human body. The mandatory participants in the collection of biological samples as a procedural action are: persons from whom biological samples are collected; officials who conduct the collection of samples and are responsible for its legality and validity; a specialist or expert; witnesses; employees of the relevant law enforcement agencies (in the case of compulsory collection of biological samples). Optional participants are a defence counsel, legal representative, representative, lawyer, doctor at their request. During the compulsory collection of biological samples, in order to ensure the legality, objectivity, reliability of the objects of expert research, preservation of health and observance of human rights, it is necessary to comply with legal, ethical, medical and forensic conditions. The author proposes a general algorithm for the tactics of obtaining biological samples for examination at the stage of pre-trial investigation, which includes the preparatory, working and final stages.

Доказано, что биологическими образцами для экспертизы являются части (ткани), выделение и отражение рельефа кожи тела человека. Определены обязательные и факультативные участники, условия и общий алгоритм тактики добровольного и принудительного отбора биологических образцов для экспертизы на стадии досудебного расследования, включающего подготовительный, рабочий и заключительный этапы проведения процессуального действия.
Biological samples for examination: concepts, conditions, sampling tactics
Keywords: кримінальне провадження; судова експертиза; біологічні зразки; примусовий відбір; умови відбирання; тактика відбирання; criminal proceedings; forensic examination; biological samples; compulsory sampling; sampling conditions; sampling tactics; уголовное производство; судебная экспертиза; биологические образцы; принудительный отбор; условия отбора; тактика отбора